Hubungan Gaya Komunikasi Tutor dengan Motivasi Belajar Peserta Didik Paket C di Homeschooling Pena Surabaya - Utami, Faza Maulidia; Susilo, Heryanto (J+PLUS UNESA, 2024)
This research aims to determine the relationship between assertive communication style and the learning motivation of package C students at Homeschooling Pena Surabaya, to find out the relationship between aggressive communication style and the learning motivation of package C students at Homeschooling Pena Surabaya, and to find out the relationship between assertive and aggressive communication styles with Learning motivation for package C students at Homeschooling Pena Surabaya. This research method is quantitative correlational with a total of 32 students as respondents. The research results show that assertive communication style has a positive relationship with learning motivation with a significance value of 0.010. Aggressive communication style has a positive relationship with learning motivation with a significance value of 0.031. So the assertive communication style has a stronger relationship with learning motivation than the aggressive communication style based on the correlation coefficient value, the assertive communication style with learning motivation is 0.448 in the quite strong category, while the aggressive communication style with learning motivation is 0.031 in the low category.